An Integrated Assessment of China's Ecological Restoration Programs - Yin, Runsheng. (Springer Netherlands, 2009)
China has been undertaking unprecedented ecological restoration efforts to deal with its problems of soil erosion, flooding, dust storms, and habitat loss. While there have been studies of these efforts, questions remain concerning whether they have been effectively implemented, what their induced socioeconomic and ecological impacts are, and how their performance can be improved. Tackling these important questions in an integrated manner, "An Integrated Assessment of Chinas Ecological Restoration Programs" is extraordinary for its broad coverage and methodological rigor. It provides a substantial improvement over the conventional approach of simply reporting projects undertaken and accepting uncritically the government assessment, and thus fills an important knowledge gap of the restoration efforts being implemented upon a variety of ecosystems in China. Not only is this volume interesting and informative in conveying a general sense of ecological improvements, but it provides useful analytical methods and innovative research advances in assessing the effectiveness and impacts of similar programs and policies.